Cape Verde : First Review Under the Policy Support Instrument. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses key findings of the First Review Under the Policy Support Instrument (PSI) for Cape Verde. The PSI seeks to reduce macroeconomic risks, provides a margin of safety against exogenous shocks, and addresses the prospect of a longer-term decline in highly concessional external support. Economic and policy performance remains strong. Growth projections for 2006 and 2007 have been revised upward, international reserves are accumulating rapidly, and inflation is falling more quickly than expected. The authorities reaffirm their commitment to the PSI policy objectives.